CLASSIFICATION OF ATRIAL FIBRILATION OR ATRIAL FLЕTTER ORIENTATED FOR PRACTICAL DOCTOR - Yabluchansky, N.I.; Martimyanova, L.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
A clinical classification of orientated on practical doctor atrial fibrillation offered. The classification comprised both well-known and completely new points. It consist of eight parts: nature, mechanisms,  flow, clinical picture and its meaning, accompanying  syndromes, important in decisions making, complications, reactions to medical interferences and drugs in acute pharmacologic tests, prognosis. Each part consists of subdivision. The classification is explained in details.